Una revisión de las aplicaciones del paradigma de equivalencia de estímulos - Fiorentini, Leticia (2012)
The paradigm of equivalence classes has been widely used to study the formation of categories and concepts. After learning of arbitrary connections between stimuli, new relations are verified experimentally spontaneously although these were not directly trained. The ability to transfer responses to stimuli within a class might be a prerequisite for language development in humans. For this reason it is considered that the equivalence classes are similar to abstract categories. This generative capacity of the paradigm gives interest in the level of the practical applications. In this communication it will be reviewed the force of such applications. In particular, there will be mentioned the different clinical and education trials in which this methodology is used. It is concluded that the paradigm is useful for both in the context of the assessment and the cognitive rehabilitation, education and psychotherapy.